Improving Learning Achievement through Group Investigation Method with eLDirU - Perwita, Dyah (Universitas Negeri Semarang, 2021)
This study aimed to improve learning achievement through the Group Investigation Method with eLDirU (e-learning of Jenderal Soedirman University). This study used a Classroom Action Research (CAR) approach. Classroom Action Research was carried out in a series of steps with 2 cycles. The research targets were students of Economic Education in the third semester of Jenderal Soedirman University in the Education Management course. The data collection techniques used observation, interview, test and documentation. The use of the Group Investigation Method and ELDirU was proven to improve learning achievement. The minimum completeness criteria set was 60 while the achievement target set was 80%. In the pre-cycle stage before the implementation of the Group Investigation Method with ELDirU, students who scored more than 60 were only 14 students or 29.78% with a class average score of 56.7. After the implementation of the Group Investigation Method with ELDirU, students who completed and had a score of more than 60 increased significantly to 37 students or 80.43% with a class average score of 72.2 in the first cycle. In the second cycle the students who completed increased again to 43 students or 93.47% with an average grade score of 86.96. The results of this study are expected to provide additional scientific references on the importance of improving the quality of e-learning in order to achieve good learning achievement.